Randomized trial of α-interferon or dexamethasone as maintenance treatment for multiple myeloma - Alexanian, R.; Weber, D.; Dimopoulos, M.; Delasalle, K.; Smith, T.L. (American Journal of Hematology, 2000)
In order to assess the role of α-interferon or dexamethasone as maintenance therapy for multiple myeloma, 172 consecutive, previously untreated patients with disease of low or intermediate tumor mass received primary therapy with oral melphalan and intermittent, high-dose dexamethasone (MD), repeated monthly. Within 5 months, 84 responding patients were assigned at random to maintenance treatment with α-interferon (3 mU s.c. 3 x weekly) or dexamethasone (20 mg/m2 p.o. each morning for 4 days) repeated monthly until relapse. Upon relapse, MD was resumed for 2 cycles and second responses were maintained with 4-day courses of melphalan-dexamethasone until second relapse. Initial response was achieved in 88 patients (51%) after a median 0.7 month and no more than 3 courses of MD, a frequency of response similar to that observed previously with dexamethasone alone. There were identical median remissions of 10 months with interferon or dexamethasone, both maintenance regimens being associated with infrequent, mild, and reversible side effects. Significantly more patients responded again to resumption of MD after disease relapse to interferon (82%) than to dexamethasone (44%) (P = 0.001). The median remission from randomization to melphalan-resistant second relapse was 32 months for patients maintained initially on interferon compared to 19 months for those on dexamethasone (P = 0.01). These findings supported an advantage for interferon in remission maintenance by increasing the frequency of tumor recontrol with later treatment that included dexamethasone. (C) 2000 Wiley-Liss, Inc.
Keywords: Dexamethasone; multiple myeloma; α-interferon